HUBUNGAN LINGKUNGAN BELAJAR DI WORKSHOP DENGAN HASIL BELAJAR MATA DIKLAT PRAKTEK KERJA KAYU SISWA PROGRAM STUDI KEAHLIAN TEKNIK BANGUNAN SMK NEGERI 2 SUNGAI PENUH - 17-26 . Debi Sandra (CIVED, 2013)
The research method is correlation analisys. The purpose of this research is study aimed to examine the correlation of condition in the learning environment with workshop wood's training practice result learning student of Skills Building Engineering Program in Vocational High School 2 Sungai Penuh. Population research derived from class XI and XII Wood Construction Engineering Skills Competency in 2012/2013. Sample taken using startified proportional random sampling. The type of data used are primary data and secondary data. The primary data obtained by distributing questionnaires to 49 students about condition in the learning environment in the workshop. The secondary data is the result of learning form the average value of the wood work practices training they receive. The result analysis is there is a significant correlation of condition in the learning environment with workshop wood's training practice result learning student of Skills Building Engineering Program in Vocational High School 2 Sungai Penuh with confidence 95 %. It can be seen from the results of the t test thitung (3.273) > ttabel (2.052) for the students of class XI and thitung (3.469) > ttabel (2.101) for the students of class XII. Based on the acquisition of the above test results, it can be concluded that better condition in the learning environment better workshop wood's training practice result learning student. Key words :        lingkungan belajar, hasil belajar, mata diklat praktek kerja kayu